Rare earth up-conversion red-green-blue fluorescence coding microsphere and preparation method thereof

The use of a modified olefin-norbornene copolymer with rare earth up-conversion luminescent nanocrystals in a fiber-drawing process addresses leakage and monodispersity issues, enabling stable, sensitive, and large-scale production of fluorescent coded microspheres for biological detection.

CN119220025AActive Publication Date: 2024-12-31ZHEJIANG UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411286201.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-31
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing methods for preparing fluorescent coded microspheres using rare earth upconversion luminescent nanocrystals face issues such as leakage, fluorescence quenching, non-specific adsorption, and poor monodispersity due to hydrophobicity and phase separation, which affect sensitivity and stability.

Method used

A method involving a modified olefin-norbornene copolymer as the matrix material, blended with rare earth up-conversion luminescent nanocrystals, is used to create a core layer that is hot-pressed and drawn into fibers, followed by heat-treatment to form stable, monodisperse microspheres with adjustable fluorescence types and intensities.

Benefits of technology

The method achieves stable fluorescence performance, large-scale production, and high sensitivity with uniform particle sizes, suitable for detecting cells and molecules in biological samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220025A_ABST
    Figure CN119220025A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth up-conversion red-green-blue fluorescence coding microsphere, which adopts a modified olefin-norbornene copolymer as a matrix material and adopts red, blue or green rare earth up-conversion luminescence nanocrystals as a fluorescence coding material. The invention also discloses a preparation method of the rare earth up-conversion red-green-blue fluorescence coding microspheres, which comprises the following steps: modifying an olefin-norbornene copolymer, and blending the modified olefin-norbornene copolymer with up-conversion luminescence nanocrystals to obtain a uniform blend; the core layer is inserted into a cladding material to prepare a prefabricated rod, and then the prefabricated rod is subjected to hot drawing to prepare fibers; and then, the fibers are subjected to heat treatment to obtain the polymer fluorescent microspheres with the coding function. According to the method disclosed by the invention, the fluorescence type and intensity of the fluorescence coding microspheres and the particle size of the microspheres can be controlled as required, the preparation process is simple, the method is suitable for large-scale production, the fluorescence performance is stable, and the method can be used for detecting cells, proteins or other molecules in biological samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluorescent coding microspheres, and in particular to rare earth up-conversion red, green and blue fluorescent coding microspheres and a preparation method thereof. Background Art

[0002] Fluorescence coded microsphere detection technology is one of the multi-index detection technologies that has received widespread attention in recent years. Fluorescence coded microspheres can realize the simultaneous identification and quantitative analysis of nucleic acids, proteins, small molecule compounds, etc. At the same time, fluorescence coded microsphere detection technology also has many advantages, such as high controllability of microsphere particle size and fluorescence intensity, high sensitivity and specificity, good biocompatibility, simple encoding and decoding, quantitative detection, high fluorescence stability, easy preparation and operation, etc. Therefore, fluorescence coded microsphere detection technology has broad application prospects in biomedicine, biopharmaceuticals, cancer diagnosis, drug release and targeted detection, monitoring of harmful substances in the environment and environmental pollution.

[0003] Compared with traditional organic fluorescent dyes and inorganic quantum dots, rare earth upconversion luminescent nanocrystals have a longer luminescence lifetime, are not easily affected by environmental factors and attenuated, have better luminescence stability, are not easily affected by light radiation and photobleaching, and usually have a narrower luminescence spectrum, which can provide a purer spectrum, etc., making them more suitable for the preparation of fluorescent coded microspheres. Polymer fluorescent microspheres loaded with rare earth upconversion luminescent nanocrystals are suitable for long-term tracking and labeling applications, and are more suitable for long-term stable fluorescent labeling, and have good fluorescence stability under various environmental conditions.

[0004] At present, the main methods for preparing fluorescent coded microspheres are swelling method, embedding method, covalent bonding method, etc. The fluorescent coded microsphere nanocrystals prepared by swelling method are easy to leak out from the inside of the microspheres, the embedding method will inevitably introduce free radicals, which will cause defects and cause obvious fluorescence quenching, the covalent bonding method has a cumbersome experimental process, and the nanocrystals are prone to non-specific adsorption on the surface of the microspheres.

[0005] In addition, research has found that olefin-norbornene copolymer materials can be used as the matrix material of fluorescent coded microspheres because of their advantages of easy processing, low production cost, easy modification of channel surface, good biocompatibility, and good chemical inertness, good optical transparency, and low fluorescence background. However, the inner wall of the olefin-norbornene copolymer channel is highly hydrophobic, and the surface of the rare earth upconversion nanocrystal has ligands, which makes it easy for phase separation to occur when the two are mixed, causing the nanocrystals to agglomerate in the molten copolymer, making the fluorescent coded microspheres poorly monodisperse and prone to adhesion, which greatly reduces the sensitivity of the fluorescent coded microspheres. Summary of the invention

[0006] In order to solve the above technical problems, the present invention discloses a rare earth up-conversion red, green and blue fluorescent coding microsphere, wherein the microsphere of the present invention adopts a modified olefin-norbornene copolymer as a matrix material, and adopts red, blue or green rare earth up-conversion luminescent nanocrystals as fluorescent coding materials. In addition, the present invention also discloses a method for preparing a rare earth up-conversion red, green and blue fluorescent coding microsphere, wherein the olefin-norbornene copolymer is modified, and then the modified olefin-norbornene copolymer is blended with the up-conversion luminescent nanocrystal to obtain a uniform blend, and then the blend is hot-pressed into a rod-shaped form as a core layer and inserted into a primary cladding rod to form a primary preform rod, and then hot-drawn into a primary fiber, and then multiple fibers are inserted into a secondary cladding rod to form a secondary preform rod, and then hot-drawn into a secondary fiber, and the secondary fiber that has been stretched for a second time is heat-treated to obtain a polymer fluorescent microsphere with a coding function. During preparation, the type and concentration of the rare earth up-conversion luminescent nanocrystal can be selected and adjusted so that the coded microsphere has fluorescence of different types and intensities, and a single-color and multi-color fluorescent coded microsphere with a super-large coding capacity is obtained. The method of the invention has a simple process flow, is suitable for large-scale production, has a large microsphere encoding capacity, and has stable fluorescence performance, and can be used to detect cells, proteins or other molecules in biological samples.

[0007] The present invention discloses a rare earth up-conversion red, green and blue fluorescence coding microsphere, comprising the following components:

[0008] Z1wt% of a modified olefin-norbornene copolymer, 75≤Z1<100;

[0009] Z2wt% red upconversion luminescent nanocrystals, 0≤Z2≤25;

[0010] Z3wt% green upconversion luminescent nanocrystals, 0≤Z3≤25;

[0011] Z4wt% blue up-conversion luminescent nanocrystals, 0≤Z4≤25; Z2, Z3, and Z4 are not all 0 at the same time;

[0012] Wherein, the modified olefin-norbornene copolymer has the structural formula:

[0013] 1≤X≤10, 1≤Y≤10, R is hydroxyl or amino.

[0014] A further technical solution is: the structural formula of the red upconversion luminescent nanocrystal is CuSc 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ ; The structural formula of green upconversion luminescent nanocrystal is K3Sr 3.76 In5F 26:0.2Yb,0.02Er,0.02Pr; the structural formula of blue upconversion luminescent nanocrystal is Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ .

[0015] The present invention also discloses a method for preparing rare earth up-conversion red, green and blue fluorescence coding microspheres, comprising the following steps:

[0016] Step 1: adding the olefin-norbornene copolymer to a toluene solution, heating and stirring at 50° C. for 25 to 40 minutes until the mixture is completely dissolved to obtain a mixed solution, and forming the mixed solution into a film by a coating machine;

[0017] Step 2: crush the film obtained in step 1 and add it into bromine water, react it under ultraviolet light for 12 hours, then pour it into alkaline solution and soak it for 24 hours, freeze-dry the solution after the reaction at -99°C to obtain a modified olefin-norbornene copolymer;

[0018] Step 3: Weigh Z1wt% of the modified olefin-norbornene copolymer of step 2, add it into a beaker filled with cyclohexane solvent and heat and stir continuously at 60°C, weigh Z2wt% of red upconversion nanocrystals, Z3wt% of green upconversion luminescent nanocrystals, and Z4wt% of blue upconversion luminescent nanocrystals and disperse them in a container filled with cyclohexane solvent, and after the modified olefin-norbornene copolymer is completely dissolved, pour the mixed solution in the container into the beaker, stir continuously for 8-12h, ultrasonicate in an ice water bath for 2-3h, and freeze-dry at -30--10°C for 15-24h to obtain a core layer material; wherein, 75≤Z1<100, 0≤Z2≤25, 0≤Z3≤25, 0≤Z4≤25; Z2, Z3, and Z4 are not 0 at the same time;

[0019] Step 4: hot-pressing the cladding material into a cylindrical primary cladding rod containing a cavity, hot-pressing the core layer material of step 3 into a cylindrical core layer rod at 230° C., placing the core layer rod into the cavity of the primary cladding rod, and then placing the primary cladding rod in a vacuum drying oven at 100° C. for 30 minutes to obtain a primary preform rod, and hot-drawing the primary preform rod at 360° C. to obtain a primary fiber;

[0020] Step 5: hot-press the cladding material into a cylindrical secondary cladding rod with a cavity inside, insert a plurality of primary fibers with the same diameter and height into the cavity of the secondary cladding rod, then put the secondary cladding rod into a vacuum drying oven and heat-cure it at 100° C. for 30 minutes to obtain a secondary preform rod, and hot-draw the secondary preform rod at 360° C. to obtain a secondary fiber;

[0021] Step 6: heat treating the secondary fiber of step 5 at 350-380° C. for 3-10 min;

[0022] Step 7: Dissolve the secondary fiber of step 6 in a selective solvent for the cladding material, heat and stir until completely dissolved, centrifuge at high speed for 5 minutes, remove the upper liquid and collect the precipitate, add the precipitate back into the selective solvent for the cladding material, and after repeated dissolution, centrifugation and filtration, fully remove the cladding material to obtain rare earth up-conversion red, green and blue fluorescent coded microspheres.

[0023] A further technical solution is: the structural formula of the red up-conversion luminescent nanocrystal is

[0024] dC 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ ; The structural formula of green upconversion luminescent nanocrystal is

[0025] K3 3.76 In5F 26 :0.2Yb,0.02Er,0.02P; the structural formula of blue upconversion luminescent nanocrystals is

[0026] oeLh 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ .

[0027] A further technical solution is: the cladding material is polysulfone resin.

[0028] A further technical solution is that the selective solvent of the cladding material is one of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide or chloroform.

[0029] A further technical solution is: the alkaline solution is one of potassium hydroxide, sodium hydroxide and ethylenediamine solution.

[0030] A further technical solution is: the film prepared in step 1 has a thickness of 200 to 400 μm.

[0031] A further technical solution is that the diameters of the primary cladding rods in step 4 and the secondary cladding rods in step 5 are 20 to 30 mm, and the diameter of the core layer rods in step 4 is 2 to 4 mm.

[0032] A further technical solution is that the diameters of the primary fibers in step 4 and the secondary fibers in step 5 are 400 to 800 μm.

[0033] A further technical solution is: the particle size of the microspheres obtained in step 7 is 5 to 10 μm.

[0034] Beneficial effects of the present invention:

[0035] The present invention modifies the olefin-norbornene copolymer and connects -OH or -NH2 functional groups to its surface through a nucleophilic substitution reaction. The surface contact angle of the modified olefin-norbornene copolymer is significantly reduced, and the strong hydrophobicity of the olefin-norbornene copolymer can be effectively reduced, thereby improving the dispersibility of the rare earth upconversion luminescent nanocrystals, and further improving the performance of the fluorescent coded microspheres. In addition, the present invention uses a solution blending method to mix the modified olefin-norbornene copolymer and the rare earth upconversion luminescent nanocrystals, further promoting the dispersibility of the rare earth upconversion luminescent nanocrystals in the modified olefin-norbornene copolymer. In addition, the present invention adopts a method for preparing the core layer of the fiber by fluid mechanics, and utilizes the instability of the fluid in the fiber, the glass transition temperature difference between the cladding material and the core material, the viscosity of the core material, and the selective dissolution of the cladding material by the solvent, so that the core layer, which is a blend of modified olefin-norbornene copolymer and rare earth upconversion luminescent nanocrystal, softens and shrinks into a polymer fluorescent microsphere. The microspheres prepared by this method have good monodispersity, uniform particle size, and a large controllable range of microsphere size, which can effectively solve the problem that fluorescent coded microspheres are prone to adhesion. The process of preparing microspheres by the method of the present invention only involves physical processes and does not involve chemical processes. Therefore, the obtained fluorescent coded microspheres highly maintain the physical and chemical properties of rare earth upconversion luminescent nanocrystals.

[0036] When preparing the microspheres of the present invention, nanocrystals of different types and concentrations can be used as coding basic materials, so that the microspheres have different types and intensities of fluorescence, and single-color and multi-color fluorescent coded microspheres with ultra-large coding capacity are obtained, realizing fluorescent coding and high-throughput detection. The particle size of the prepared microspheres can also be adjusted by controlling the number of fiber stretching times, thereby meeting the needs of various experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The particle size distribution and scanning electron microscope image of the pure red fluorescent encoded microspheres of Example 1;

[0038] Figure 2 The fluorescence spectrum of the pure red fluorescent coded microspheres in Example 1;

[0039] Figure 3 The particle size distribution and scanning electron microscope image of the pure green fluorescent encoded microspheres of Example 2;

[0040] Figure 4 The fluorescence spectrum of the pure green fluorescence coded microspheres in Example 2;

[0041] Figure 5The particle size distribution and scanning electron microscope image of the pure blue fluorescent coded microspheres of Example 3;

[0042] Figure 6 The fluorescence spectrum of the pure blue fluorescent coded microspheres of Example 3;

[0043] Figure 7 This is the up-conversion fluorescence spectrum of the red and green dual-color fluorescence coded microspheres of Example 4;

[0044] Figure 8 This is the up-conversion fluorescence spectrum of the red and blue dual-color fluorescent coded microspheres of Example 5;

[0045] Fig. 9 This is the up-conversion fluorescence spectrum of the green and blue dual-color fluorescent coded microspheres of Example 6;

[0046] Fig.10 The morphology of the red, green and blue multicolor fluorescent coded microspheres of Example 7 under an optical microscope and their particle size distribution histogram;

[0047] Fig.11 This is an up-conversion fluorescence spectrum of the red, green and blue multicolor fluorescent coded microspheres of Example 7;

[0048] Fig.12 Schematic diagram of the three-dimensional matrix coding constructed by the multi-color fluorescent coding microspheres prepared in Examples 1-7. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] (1) Weigh 1 g of olefin-norbornene copolymer and pour it into a beaker containing 20 mL of toluene solution. Stir and heat at 50° C. for 30 min to completely dissolve the olefin-norbornene copolymer to obtain a mixed solution. Use a coater to form a film with a thickness of about 400 μm.

[0052] (2) Cut the obtained film into pieces and pour it into 3% bromine water, react it under ultraviolet light for 12 hours to perform bromide modification on the olefin-norbornene copolymer, then pour the brominated olefin-norbornene copolymer into 1M potassium hydroxide solution and soak it for 24 hours, connect the -OH functional group on the surface of the olefin-norbornene copolymer through nucleophilic substitution reaction, and then freeze-dry the solution after the reaction at -99°C for 24 hours to obtain a modified olefin-norbornene copolymer, whose structural formula is Wherein X=Y=5, and R is a hydroxyl group.

[0053] The relevant properties of the obtained product were characterized. The surface contact angle of the unmodified olefin-norbornene copolymer was about 92°, and the surface contact angle of the modified olefin-norbornene copolymer was 45°. The results showed that the hydrophobicity of the modified olefin-norbornene copolymer was significantly reduced.

[0054] (3) 1 g of the modified olefin-norbornene copolymer obtained in step (2) was placed in a beaker containing 20 mL of cyclohexane, and the mixture was heated at 60° C. and stirred continuously for 60 min to fully dissolve the modified olefin-norbornene copolymer. Then 0.01 g of the structural formula CuSc was taken. 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ Pure red upconversion luminescent nanocrystals were dispersed in a container containing 1 mL of cyclohexane solvent. After the modified olefin-norbornene copolymer was completely dissolved, the solution in the container was poured into a beaker and stirred continuously for 12 h. Then, the pure red upconversion luminescent nanocrystals were evenly dispersed in the mixed solution containing the modified olefin-norbornene copolymer in an ice-water bath for 2 h. Finally, the pure red upconversion luminescent nanocrystals were freeze-dried at -15 °C for 22 h to fully remove the cyclohexane. The product was collected to obtain the core layer material as a precursor of the red fluorescent coded microspheres. The pure red upconversion luminescent nanocrystals accounted for about 1 wt%.

[0055] (4) Using a cylindrical mold, hot-pressing the polysulfone resin at 300° C. into a cylindrical primary cladding rod containing a cavity, the diameter of the primary cladding rod is 20 mm, and the diameter of the cavity in the primary cladding rod is 2 mm. Using a cylindrical mold, hot-pressing the core layer material obtained in step (3) at 230° C. into a core layer rod with a diameter of 2 mm. After the core layer rod is inserted into the cavity in the primary cladding rod as a fiber core, the primary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a primary preform. The primary preform is placed on a drawing tower and hot-drawn at 360° C. into a primary fiber with a diameter of 600 μm.

[0056] (5) The polysulfone resin material is hot pressed at 310° C. into a secondary cladding rod with a diameter of 30 mm, wherein a cavity with a diameter of 6 mm is provided in the secondary cladding rod, 70 fibers having highly consistent diameters after the heat treatment in step (5) are selected and inserted into the cavity of the secondary cladding rod, and then the secondary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a secondary preform rod, and the secondary preform rod is placed on a drawing tower and heat-drawn at 360° C. into a secondary fiber with a diameter of 600 μm.

[0057] (6) The secondary fiber of step (5) is placed in a tubular furnace and heat treated at 380° C. for 8 minutes, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0058] (7) Place the secondary fiber of step (6) into a beaker containing 50 mL of N, N-dimethylacetamide solvent, stir continuously at 80°C, and after the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13000 rpm for 5 minutes, extract the upper liquid and collect the precipitate. Add the precipitate back into the N, N-dimethylacetamide solvent, repeat the above dissolution, centrifugation and filtration operations 8 times to fully remove the polysulfone resin cladding material, and finally obtain pure red fluorescent coded microspheres with a particle size of 7 μm. It can be observed from Figure 1 that the pure red fluorescent coded microspheres have good morphology and structure and have excellent monodispersity and particle size uniformity. The microspheres are regular and smooth in shape without adhesion.

[0059] Example 2

[0060] (1) Weigh 1 g of olefin-norbornene copolymer and pour it into a beaker containing 30 mL of toluene solution. Stir and heat at 50° C. for 25 min to completely dissolve the olefin-norbornene copolymer to obtain a mixed solution. Use a coater to form a film with a thickness of about 200 μm.

[0061] (2) Cut the obtained film into pieces and pour it into 3% bromine water, react it under ultraviolet light for 12 hours to perform bromide modification on the olefin-norbornene copolymer, then pour the brominated olefin-norbornene copolymer into 1M potassium hydroxide solution and soak it for 24 hours, connect the -OH functional group on the surface of the olefin-norbornene copolymer through nucleophilic substitution reaction, and then freeze-dry the solution after the reaction at -99°C for 24 hours to obtain a modified olefin-norbornene copolymer, whose structural formula is Wherein X=Y=5, and R is a hydroxyl group.

[0062] The relevant properties of the obtained product were characterized. The surface contact angle of the unmodified olefin-norbornene copolymer was about 92°, and the surface contact angle of the modified olefin-norbornene copolymer was 42°. The results showed that the hydrophobicity of the modified olefin-norbornene copolymer was significantly reduced.

[0063] (3) 1 g of the modified olefin-norbornene copolymer obtained in step (2) was placed in a beaker containing 40 mL of cyclohexane and stirred continuously at 60° C. for 20 min to fully dissolve the modified olefin-norbornene copolymer. Then 0.005 g of the structural formula K3Sr 3.76 In5F 26 : 0.2Yb, 0.02Er, 0.02Pr pure green upconversion luminescent nanocrystals were dispersed in a container filled with 1mL of cyclohexane solvent. After the modified olefin-norbornene copolymer was completely dissolved, the solution in the container was poured into a beaker and stirred continuously for 12h. Then, the pure green upconversion luminescent nanocrystals were evenly dispersed in the mixed solution containing the modified olefin-norbornene copolymer in an ice-water bath for 2h. Finally, they were freeze-dried at -20℃ for 24h to fully remove the cyclohexane. The product was collected to obtain the core layer material as a precursor of green fluorescent coded microspheres. The proportion of pure green upconversion luminescent nanocrystals was about 0.5wt%.

[0064] (4) Using a cylindrical mold, hot-press the polysulfone resin at 290° C. to form a cylindrical primary cladding rod containing a cavity, wherein the diameter of the primary cladding rod is 20 mm, the diameter of the cavity in the primary cladding rod is 2 mm, and the cavity is arranged along the length direction of the primary cladding rod. Using a cylindrical mold, hot-press the core layer material obtained in step (3) at 230° C. to form a core layer rod with a diameter of 2 mm. After the core layer rod is inserted into the cavity of the primary cladding rod as a fiber core, the primary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a primary preform. The primary preform obtained in step (4) is placed on a drawing tower and hot-drawn at 360° C. to form a primary fiber with a diameter of 400 μm.

[0065] (5) The polysulfone resin material is hot-pressed at 300° C. into a secondary cladding rod with a diameter of 20 mm, wherein a cavity with a diameter of 6 mm is provided in the secondary cladding rod, 70 primary fibers of step (4) with highly consistent diameters are selected and inserted into the cavity of the secondary cladding rod, and then the secondary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a secondary preform rod, and the secondary preform rod is placed on a drawing tower and heat-drawn at 360° C. into a secondary fiber with a diameter of 400 μm.

[0066] (6) The secondary fiber of step (5) is placed in a tubular furnace and heat treated at 280° C. for 5 minutes, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0067] (7) Place the secondary fiber of step (6) in a beaker containing 50 mL of N,N-dimethylacetamide solvent and stir continuously at 80°C. After the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13,000 rpm for 5 minutes, extract the upper liquid and collect the precipitate. Add the precipitate back into the N,N-dimethylacetamide solvent and repeat the above dissolution, centrifugation and filtration operations 7 times to fully remove the polysulfone resin cladding material. Figure 3 and Figure 4 As shown, pure green fluorescent coded microspheres with a particle size of 6 μm were finally obtained.

[0068] It can be observed from FIG. 3 that the green fluorescent encoded microspheres have good morphology and structure and excellent monodispersity and particle size uniformity. The microspheres have good morphology and structure and a smooth surface.

[0069] Example 3

[0070] (1) Weigh 1 g of olefin-norbornene copolymer and pour it into a beaker containing 40 mL of toluene solution. Stir and heat at 50° C. for 30 min to completely dissolve the olefin-norbornene copolymer to obtain a mixed solution. Use a coater to form a film with a thickness of about 300 μm.

[0071] (2) Cut the obtained film into pieces and pour it into 3% bromine water, react it under ultraviolet light for 12 hours to perform bromide modification on the olefin-norbornene copolymer, then pour the brominated olefin-norbornene copolymer into 10% ethylenediamine aqueous solution and soak it for 24 hours, connect the -NH2 functional group on the surface of the olefin-norbornene copolymer through substitution reaction, then freeze-dry the solution after the reaction at -99°C for 24 hours to obtain a modified olefin-norbornene copolymer, whose structural formula is Wherein X=Y=5, and R is an amino group.

[0072] The relevant properties of the obtained product were characterized. The surface contact angle of the unmodified olefin-norbornene copolymer was about 92°, and the surface contact angle of the modified olefin-norbornene copolymer was 41°. The results showed that the hydrophobicity of the modified olefin-norbornene copolymer was significantly reduced.

[0073] (3) 1 g of the modified olefin-norbornene copolymer obtained in step (2) was placed in a beaker containing 30 mL of cyclohexane and stirred continuously at 60° C. for 50 min to fully dissolve the modified olefin-norbornene copolymer. Then 0.15 g of Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+Pure blue upconversion luminescent nanocrystals were dispersed in a container containing 1 mL of cyclohexane solvent. After the modified olefin-norbornene copolymer was completely dissolved, the solution in the container was poured into a beaker and stirred continuously for 12 h. Then, the pure blue upconversion luminescent nanocrystals were evenly dispersed in the mixed solution containing the modified olefin-norbornene copolymer in an ice-water bath for 2 h. Finally, the pure blue upconversion luminescent nanocrystals were freeze-dried at -30 ° C for 24 h to fully remove the cyclohexane. The product was collected to obtain the core layer material as a precursor of the blue fluorescent coded microspheres. The pure blue upconversion luminescent nanocrystals accounted for about 13 wt%.

[0074] (4) Using a cylindrical mold, hot-pressing the polysulfone resin at 300° C. into a cylindrical primary cladding rod containing a cavity, the diameter of the primary cladding rod is 30 mm, and the diameter of the cavity in the primary cladding rod is 2 mm. Using a cylindrical mold, hot-pressing the core layer material obtained in step (3) at 230° C. into a core layer rod with a diameter of 2 mm. After the core layer rod is inserted into the cavity in the primary cladding rod as a fiber core, the primary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a primary preform. The primary preform is placed on a drawing tower and hot-drawn at 360° C. into a primary fiber with a diameter of 500 μm.

[0075] (5) The polysulfone resin material is hot-pressed at 310° C. into a secondary cladding rod with a diameter of 30 mm, wherein a cavity with a diameter of 6 mm is provided in the secondary cladding rod, and 80 primary fibers of step (4) with highly consistent diameters are selected and inserted into the cavity of the secondary cladding rod. The secondary cladding rod is then placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a secondary preform rod, and the secondary preform rod is placed on a drawing tower and heat-drawn at 360° C. into a secondary fiber with a diameter of 500 μm.

[0076] (6) The secondary fiber is placed in a tubular furnace and heat treated at 380°C for 8 minutes, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0077] (7) Place the secondary fiber of step (6) into a beaker containing 50 mL of N, N-dimethylacetamide solvent, stir continuously at 80°C, and after the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13000 rpm for 5 minutes, extract the upper liquid and collect the precipitate. Add the precipitate back into the N, N-dimethylacetamide solvent, repeat the above dissolution, centrifugation and filtration operations 8 times to fully remove the polysulfone resin cladding material, and finally obtain pure blue fluorescent coded microspheres with a particle size of 5 μm. It can be observed from Figure 5 that the pure blue fluorescent coded microspheres have good morphology and structure and have excellent monodispersity and particle size uniformity. The microspheres are regular and smooth in shape without adhesion.

[0078] Example 4

[0079] Steps 1 and 2 in Example 4 are exactly the same as Steps 1 and 2 in Example 3, and the modification process and component ratio of the olefin-norbornene copolymer are the same, which will not be repeated here.

[0080] (3) 1 g of the modified olefin-norbornene copolymer obtained in step (2) was placed in a beaker containing 35 mL of cyclohexane and stirred continuously for 35 min at 60° C. to fully dissolve the modified olefin-norbornene copolymer. Then 0.1 g of the structural formula CuSc was taken. 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ Pure red upconversion luminescent nanocrystals and 0.1g of the structural formula K3Sr 3.76 In5F 26 : 0.2Yb, 0.02Er, 0.02Pr pure green upconversion luminescent nanocrystals were dispersed in a container containing 1mL of cyclohexane solvent. After the modified olefin-norbornene copolymer was completely dissolved, the solution in the container was poured into a beaker and stirred continuously for 12h. Then, the nanocrystals were ultrasonicated in an ice-water bath for 2h to uniformly disperse the nanocrystals in the mixed solution containing the modified olefin-norbornene copolymer. Finally, they were freeze-dried at -20℃ for 24h to fully remove the cyclohexane. The products were collected to obtain the core layer material as the precursor of red and green dual-color fluorescent coded microspheres. The red and green upconversion luminescent nanocrystals accounted for about 16.7wt%.

[0081] (4) Using a cylindrical mold, hot-pressing the polysulfone resin at 500° C. into a cylindrical primary cladding rod containing a cavity, the diameter of the primary cladding rod is 30 mm, the diameter of the cavity in the primary cladding rod is 2 mm, and the cavity is arranged along the length direction of the cladding rod. Using a cylindrical mold, hot-pressing the core layer material obtained in step (3) at 230° C. into a core layer rod with a diameter of 2 mm, inserting the core layer rod into the cavity of the primary cladding rod as a fiber core, and then placing the primary cladding rod in a vacuum drying oven and heat-curing at 100° C. for 30 minutes to obtain a primary preform rod. The primary preform rod is placed on a drawing tower and hot-drawn at 360° C. into a primary fiber with a diameter of 600 μm.

[0082] (5) The polysulfone resin cladding material is hot pressed at 300° C. to form a secondary cladding rod with a diameter of 20 mm, wherein a cavity with a diameter of 6 mm is provided in the secondary cladding rod, 70 primary fibers of step (4) with highly consistent diameters are selected and inserted into the cavity of the secondary cladding rod, and then the secondary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a secondary preform rod, and the secondary preform rod is placed on a drawing tower and heat-drawn at 360° C. to form a secondary fiber with a diameter of 600 μm.

[0083] (6) The secondary fiber is placed in a tubular furnace and heat treated at 380°C for 10 min, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0084] (7) Place the secondary fiber of step (6) in a beaker containing 50 mL of N,N-dimethylacetamide solvent and stir continuously at 80°C. After the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13,000 rpm for 5 minutes, extract the upper liquid and collect the precipitate. Add the precipitate back into the N,N-dimethylacetamide solvent and repeat the above dissolution, centrifugation and filtration operations 7 times to fully remove the polysulfone resin cladding material. Figure 7 As shown, red and green dual-color fluorescent coded microspheres with a particle size of 10 μm were finally obtained.

[0085] Example 5

[0086] Steps 1 and 2 in Example 5 are exactly the same as Steps 1 and 2 in Example 3, and the modification process and component ratio of the olefin-norbornene copolymer are the same, which will not be repeated here.

[0087] (3) Take 1 g of the modified olefin-norbornene copolymer obtained in step (2) and put it into a beaker containing 20 mL of cyclohexane. Stir continuously for 55 min at 60° C. to fully dissolve the modified olefin-norbornene copolymer. Then take 0.1 g of CuSc 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ Pure red upconversion luminescent nanocrystals and 0.15g of the structural formula Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ Pure blue upconversion luminescent nanocrystals were dispersed in a container containing 1 mL of cyclohexane solvent. After the modified olefin-norbornene copolymer was completely dissolved, the solution in the container was poured into a beaker and stirred continuously for 12 h. Then, the nanocrystals were evenly dispersed in the mixed solution containing the modified olefin-norbornene copolymer in an ice-water bath for 2 h. Finally, the nanocrystals were freeze-dried at -10 °C for 24 h to fully remove the cyclohexane. The product was collected to obtain the core layer material as a precursor of the red and blue dual-color fluorescent coded microspheres. The red and blue dual-color upconversion luminescent nanocrystals accounted for 20 wt%.

[0088] (4) Using a cylindrical mold, hot-pressing the polysulfone resin at 500° C. into a cylindrical primary cladding rod containing a cavity, wherein the diameter of the primary cladding rod is 25 mm, the diameter of the cavity in the primary cladding rod is 2 mm, and the cavity is arranged along the length direction of the primary cladding rod; using a cylindrical mold, hot-pressing the core layer material obtained in step (3) at 230° C. into a core layer rod with a diameter of 2 mm; after the core layer rod is inserted into the cavity of the primary cladding rod as a fiber core, the primary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a primary preform rod; the primary preform rod is placed on a drawing tower and heat-drawn at 360° C. into a primary fiber with a diameter of 600 μm.

[0089] (5) A polysulfone resin cladding material is hot-pressed at 300° C. to form a secondary cladding rod with a diameter of 20 mm, wherein a cavity with a diameter of 6 mm is provided in the secondary cladding rod, and 70 primary fibers of step (4) with highly consistent diameters are selected and inserted into the cavity of the secondary cladding rod. The secondary cladding rod is then placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a secondary preform rod, and the secondary preform rod is placed on a drawing tower and heat-drawn at 360° C. to form a secondary fiber with a diameter of 600 μm.

[0090] (6) The secondary fiber of step (5) is placed in a tubular furnace and heat treated at 380° C. for 10 min, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0091] (7) Place the secondary fiber of step (6) in a beaker containing 50 mL of N,N-dimethylacetamide solvent and stir continuously at 80°C. After the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13,000 rpm for 5 minutes, extract the upper liquid and collect the precipitate. Add the precipitate back into the N,N-dimethylacetamide solvent and repeat the above dissolution, centrifugation and filtration operations 6 times to fully remove the polysulfone resin cladding material. Figure 8 As shown, red and blue dual-color fluorescent coded microspheres with a particle size of 10 μm were finally obtained.

[0092] Example 6

[0093] Steps 1 and 2 in Example 6 are exactly the same as Steps 1 and 2 in Example 3, and the modification process and component ratio of the olefin-norbornene copolymer are the same, which will not be repeated here.

[0094] (3) 1 g of the modified olefin-norbornene copolymer obtained in step (2) was placed in a beaker containing 40 mL of cyclohexane and stirred continuously for 30 min at 60° C. to fully dissolve the modified olefin-norbornene copolymer. Then 0.05 g of the structural formula K3Sr 3.76 In5F 26: 0.2Yb, 0.02Er, 0.02Pr pure green upconversion luminescent nanocrystals and 0.15g Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ Pure blue upconversion luminescent nanocrystals were dispersed in a container containing 1 mL of cyclohexane solvent. After the modified olefin-norbornene copolymer was completely dissolved, the solution in the container was poured into a beaker and stirred continuously for 12 h. Then, the nanocrystals were evenly dispersed in the mixed solution containing the modified olefin-norbornene copolymer in an ice-water bath for 2 h. Finally, they were freeze-dried at -10 °C for 24 h to fully remove the cyclohexane. The product was collected to obtain the core layer material as a precursor of the red and green fluorescent coding microspheres. The blue and green upconversion luminescent nanocrystals accounted for 16.7 wt%.

[0095] (4) Using a cylindrical mold, hot-pressing the polysulfone resin at 500° C. into a cylindrical primary cladding rod containing a cavity, wherein the diameter of the primary cladding rod is 25 mm, and the diameter of the cavity inside the primary cladding rod is 2 mm; using a cylindrical mold, hot-pressing the core layer material obtained in step (3) at 230° C. into a core layer rod with a diameter of 2 mm; after the core layer rod is inserted into the cavity of the primary cladding rod as a fiber core, the primary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 min to obtain a primary preform rod; the primary preform rod is placed on a drawing tower and heat-drawn at 360° C. into a primary fiber with a diameter of 600 μm.

[0096] (5) A polysulfone resin cladding material is hot-pressed at 300°C to form a secondary cladding rod with a diameter of 20 mm. A cylindrical cavity with a diameter of 6 mm is provided in the secondary cladding rod. 70 primary fibers with highly consistent diameters are selected and inserted into the cavity of the secondary cladding rod. The secondary cladding rod is then placed in a vacuum drying oven and heat-cured at 100°C for 30 minutes to obtain a secondary preform rod. The secondary preform rod is placed on a drawing tower and heat-drawn at 360°C to form a secondary fiber with a diameter of 600 μm.

[0097] (6) The secondary fiber is placed in a tubular furnace and heat treated at 380°C for 10 min, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0098] (7) Place the secondary fiber of step (6) in a beaker containing 50 mL of N,N-dimethylacetamide solvent and stir continuously at 80°C. After the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13,000 rpm for 5 minutes, extract the upper liquid and collect the precipitate. Add the precipitate back into the N,N-dimethylacetamide solvent and repeat the above dissolution, centrifugation and filtration operations 6 times to fully remove the polysulfone resin cladding material. Fig. 9As shown, blue and green dual-color fluorescent coded microspheres with a particle size of 10 μm were finally obtained.

[0099] Example 7

[0100] Steps 1 and 2 in Example 7 are exactly the same as Steps 1 and 2 in Example 3, and the modification process and component ratio of the olefin-norbornene copolymer are the same, which will not be repeated here.

[0101] (3) Take 1 g of the modified olefin-norbornene copolymer obtained in step (2) and put it into a beaker containing 35 mL of cyclohexane. Stir continuously for 40 min at 60°C to fully dissolve the modified olefin-norbornene copolymer. Then take 0.05 g of CuSc 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ Pure red upconversion luminescent nanocrystals, 0.05g of the structural formula is K3Sr 3.76 In5F 26 : 0.2Yb, 0.02Er, 0.02Pr pure green upconversion luminescent nanocrystals and 0.15g of the structural formula Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ Pure blue upconversion luminescent nanocrystals are dispersed in a container containing 1 mL of cyclohexane solvent. After the modified olefin-norbornene copolymer is completely dissolved, the solution in the container is poured into a beaker and stirred continuously for 12 hours. Then, the nanocrystals are evenly dispersed in the mixed solution containing the modified olefin-norbornene copolymer in an ice-water bath for 2 hours. Finally, the nanocrystals are freeze-dried at -30°C for 15 hours to fully remove the cyclohexane. The product is collected to obtain the core material as a precursor of red, green, and blue fluorescent coding microspheres. The red, green, and blue upconversion luminescent nanocrystals account for about 20wt%.

[0102] (4) Using a cylindrical mold, hot-pressing the polysulfone resin at 300° C. into a cylindrical primary cladding rod containing a cavity, wherein the diameter of the primary cladding rod is 25 mm, the diameter of the cavity inside the primary cladding rod is 2 mm, and the cavity is arranged along the length direction of the primary cladding rod; using a cylindrical mold, hot-pressing the core layer material obtained in step (3) at 230° C. into a core layer rod with a diameter of 2 mm; after the core layer rod is inserted into the cavity of the primary cladding rod as a fiber core, the primary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 min to obtain a primary preform rod; the primary preform rod is placed on a drawing tower and heat-drawn at 360° C. into a primary fiber with a diameter of 600 μm.

[0103] (5) A polysulfone resin cladding material is hot-pressed at 300° C. to form a secondary cladding rod with a diameter of 20 mm, wherein a cylindrical cavity with a diameter of 6 mm is provided in the secondary cladding rod, 70 primary fibers of step (4) with highly consistent diameters are selected and inserted into the cavity of the secondary cladding rod, and then the secondary cladding rod is placed in a vacuum drying oven and heat-cured at 100° C. for 30 minutes to obtain a secondary preform rod, and the secondary preform rod is placed on a drawing tower and heat-drawn at 360° C. to form a secondary fiber with a diameter of 600 μm.

[0104] (6) The secondary fiber is placed in a tubular furnace and heat treated at 380°C for 10 min, so that the core of the secondary fiber reaches the glass transition temperature to form a fluid and shrinks into a microsphere under the action of elastic force.

[0105] (7) Place the secondary fiber in a beaker containing 50 mL of N,N-dimethylacetamide solvent and stir continuously at 80°C. After the polysulfone resin cladding material is fully dissolved, centrifuge the mixed solution at 13,000 rpm for 5 min, extract the upper liquid and collect the precipitate. Add the precipitate back into the N,N-dimethylacetamide solvent and repeat the above dissolution, centrifugation and filtration operations 6 times to fully remove the polysulfone resin cladding material. Fig.10 and Fig.11 As shown, red, green and blue multicolor fluorescent coded microspheres with a particle size of about 7 μm were obtained.

[0106] from Fig.10 It can be observed that the red, green and blue multicolor fluorescent coded microspheres have good monodispersity, excellent particle size uniformity and morphology structure.

[0107] like Fig.12 As shown, the three-dimensional matrix code constructed by the fluorescent coded microspheres of different colors and intensities in Examples 1 to 7, the coordinate values ​​of the X, Y, and Z axes respectively reflect the distribution of the green, blue, and red color signals, and the density of each black dot in the three-dimensional space reflects the strength of the fluorescent intensity signal. Through this method, single-color and multi-color fluorescent coded microspheres with ultra-large coding capacity are obtained, which can realize fluorescent coding for various needs.

[0108] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A rare earth up-conversion red, green and blue fluorescence coding microsphere, characterized in that: Includes the following components: Z1wt% of a modified olefin-norbornene copolymer, 75≤Z1<100; Z2wt% red upconversion luminescent nanocrystals, 0≤Z2≤25; Z3wt% green upconversion luminescent nanocrystals, 0≤Z3≤25; Z4wt% blue up-conversion luminescent nanocrystals, 0≤Z4≤25; Z2, Z3, and Z4 are not all 0 at the same time; Wherein, the modified olefin-norbornene copolymer has the structural formula: 1≤X≤10, 1≤Y≤10, R is hydroxyl or amino.

2. The rare earth up-conversion red, green and blue fluorescence coded microsphere according to claim 1, characterized in that: The structural formula of red upconversion luminescent nanocrystals is CuSc 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ ; The structural formula of green upconversion luminescent nanocrystal is K3Sr 3.76 In5F 26 :0.2Yb,0.02Er,0.02Pr; the structural formula of blue upconversion luminescent nanocrystal is Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ .

3. A method for preparing rare earth up-conversion red, green and blue fluorescence coded microspheres, characterized in that: The steps include: Step 1: adding the olefin-norbornene copolymer to a toluene solution, heating and stirring at 50° C. for 25 to 40 minutes until the mixture is completely dissolved to obtain a mixed solution, and forming the mixed solution into a film by a coating machine; Step 2: crush the film obtained in step 1 and add it into bromine water, react it under ultraviolet light for 12 hours, then pour it into alkaline solution and soak it for 24 hours, freeze-dry the solution after the reaction at -99°C to obtain a modified olefin-norbornene copolymer; Step 3: Weigh Z1wt% of the modified olefin-norbornene copolymer of step 2, add it into a beaker filled with cyclohexane solvent and heat and stir continuously at 60°C, weigh Z2wt% of red upconversion nanocrystals, Z3wt% of green upconversion luminescent nanocrystals, and Z4wt% of blue upconversion luminescent nanocrystals and disperse them in a container filled with cyclohexane solvent, and pour the mixed solution in the container into the beaker after the modified olefin-norbornene copolymer is completely dissolved, stir continuously for 8-12h, ultrasonicate in an ice water bath for 2-3h, and freeze-dry at -30--10°C for 15-24h to obtain a core layer material; wherein, 75≤Z1<100, 0≤Z2≤25, 0≤Z3≤25, 0≤Z4≤25; Z2, Z3, and Z4 are not 0 at the same time; Step 4: hot-pressing the cladding material into a cylindrical primary cladding rod containing a cavity, hot-pressing the core layer material of step 3 into a cylindrical core layer rod at 230° C., placing the core layer rod into the cavity of the primary cladding rod, and then placing the primary cladding rod in a vacuum drying oven at 100° C. for 30 minutes to obtain a primary preform rod, and hot-drawing the primary preform rod at 360° C. to obtain a primary fiber; Step 5: hot-press the cladding material into a cylindrical secondary cladding rod with a cavity inside, insert a plurality of primary fibers with the same diameter and height into the cavity of the secondary cladding rod, then put the secondary cladding rod into a vacuum drying oven and heat-cure it at 100° C. for 30 minutes to obtain a secondary preform rod, and hot-draw the secondary preform rod at 360° C. to obtain a secondary fiber; Step 6: heat treating the secondary fiber of step 5 at 350-380° C. for 3-10 min; Step 7: Dissolve the secondary fiber of step 6 in a selective solvent for the cladding material, heat and stir until completely dissolved, centrifuge at high speed for 5 minutes, remove the upper liquid and collect the precipitate, add the precipitate back into the selective solvent for the cladding material, and after repeated dissolution, centrifugation and filtration, fully remove the cladding material to obtain rare earth up-conversion red, green and blue fluorescent coded microspheres.

4. The method for preparing rare earth up-conversion red, green and blue fluorescence coded microspheres according to claim 3, characterized in that: The structural formula of the red up-conversion luminescent nanocrystal is CuSc 0.81 In 0.99 F8:0.19Er 3+ ,0.01Mg 2+ ; The structural formula of green upconversion luminescent nanocrystal is K3Sr 3.76 In5F 26 :0.2Yb,0.02Er,0.02P; the structural formula of blue upconversion luminescent nanocrystal is Ni8Sc 2.45 Al 2.55 F8:0.55Tm 3+ ,0.45Mg 2+ .

5. The method for preparing rare earth up-conversion red, green and blue fluorescence coded microspheres according to claim 3, characterized in that: The cladding material is polysulfone resin.

6. The method for preparing rare earth up-conversion red, green and blue fluorescence coded microspheres according to claim 5, characterized in that: The selective solvent of the cladding material is one of N,N-dimethylacetamide, N-methylpyrrolidone, N,N-dimethylformamide or chloroform.

7. The method for preparing rare earth up-conversion red, green and blue fluorescence coded microspheres according to claim 3, characterized in that: The alkaline solution is one of potassium hydroxide, sodium hydroxide and ethylenediamine solution.

Citation Information

Patent Citations

  • Preparation method of fluorescent coding microspheres based on up-conversion luminous nanocrystalline

    CN102172497A

  • Rare earth-doped upconversion nanometer crystal-based fluorescent coding microspheres and preparation method thereof

    CN102199428A

  • Preparation method of polygenetic upconversion magnetic coding microspheres for screening pathogenic bacteria

    CN104707544A

  • Pure green up-conversion luminescent nano material and preparation method thereof

    CN116426277A

  • Pure red up-conversion luminescent nano material and preparation method thereof

    CN116445163A